The Effect Project Based Learning Model Based E-Learning on Students' Critical Thinking Skills: A – Meta-analysis - Sudrajat Sudrajat; Muhammad Isa Anshory; Abdul Rahman; Hardiansyah Ma’sum; Siti Aisyah; Tomi Apra Santosa (Edumaspul: Jurnal Pendidikan, 2023)
This study aims to determine the effect of project-based learning model based on e-learning on students' critical thinking skills. This research is a type of meta-analysis research. The data sources in this study came from 12 articles obtained from the journal database published from 2016-2023. Of these. The process of searching data through Google Scholar, Wiley, ScienceDirect and ERIC. The data filtering process was carried out using the PRISMA method. Data analysis is quantitative analysis by calculating the effect size value of the article with the help of the Comprehensive Meta-analysis (CMA) version 3.0 application. The results of the analysis of 12 articles showed that the overall effect size of the e-learning-based project-based learning model was statistically significant (0.857; P < 0.001; 95 % CI (0.834; 1.416). This finding shows that the implementation of project-based learning model based on E-Learning provides a high influence on students' critical thinking skills. The findings of this meta-analysis contribute greatly to the development of critical thinking skills.